Analysis of Management Services Modeling Flat Surabaya and the Impact on the Comfort of the Residents - Dimas Ade Pranata; Muhammad Ikhsan Setiawan (Journal of World Conference (JWC), 2022)
In the era of globalization, the rapid development of development is followed by increasingly varied processes from planning, implementation, to building maintenance. Building maintenance is carried out to maintain, update and repair all building components in accordance with predetermined standards. However, increasing building construction is generally not accompanied by good maintenance. This study aims to determine the maintenance of Surabaya Flats. This research refers to the (Settlements, Directorate General of Human Regulation of the Minister of Public Works Number: 24/PRT/M/2008 Concerning Guidelines for Building Maintenance and Maintenance, Ministry of Public Works, 2008) concerning Guidelines for Building Maintenance and Maintenance. The research data was obtained by distributing questionnaires to the residents of the Flats with a total of 18 respondents. Data analysis was carried out using the mean and standard deviation methods to determine whether or not there were maintenance and maintenance activities in the Surabaya Flats building. Based on the results of the analysis, the maintenance division of the Surabaya Flats got a mean value of 0.888 (very good).